Jugular Anomalies in Multiple Sclerosis Are Associated with Increased Collateral Venous Flow - Sethi, S.K. (AJNR Am J Neuroradiol, 2017)
BACKGROUND AND PURPOSE: To date, research on extracranial venous collaterals has been focused on structure, with relatively little attention paid to hemodynamics. We addressed this limitation by quantitatively comparing collateral flow in patients with multiple sclerosis and healthy controls by using phase-contrast MR imaging. We hypothesize that patients with MS with structurally anomalous internal jugular veins will have elevated collateral venous flow compared with healthy controls. MATERIALS AND METHODS: The sample consisted of 276 patients with MS and 106 healthy controls. We used MRV to classify internal jugular veins as stenotic and nonstenotic based on an absolute cross-sectional area threshold in 276 patients with MS and 60 healthy controls; 46 healthy controls lacked this imaging. Individual and total vessel flows were quantified by using phase-contrast MR imaging on all patients. Veins were classified by extracranial drainage type: internal jugular veins (I), paraspinal (II), and superficial (III). Differences among healthy controls, patients with MS, nonstenotic patients, and stenotic subgroups in total venous flow by vessel type were evaluated in a general linear model for statistical analysis. RESULTS: In the MS group, 153 patients (55%) evidenced stenosis, whereas 12 (20%) healthy controls were classified as stenotic (P < .001). Compared with healthy controls, the MS group showed lower type I flow and increased type II flow. Stenosis was associated with reduced flow in the type I vessels [F(1272) = 68; P < .001]. The stenotic MS group had increased flow in the type II vessels compared with the nonstenotic MS group [F(1272) = 67; P < .001]. CONCLUSIONS: Compared with healthy controls, patients with MS exhibit reduced venous flow in the main extracerebral drainage vein (internal jugular vein). In contrast, flow in the paraspinal venous collaterals is elevated in patients with MS and exacerbated by venous stenosis. Collateral drainage may be a compensatory response to internal jugular vein flow reduction.